Effect of the Synthesit Dietary Supplement on Serum Cholesterol Levels - Patrik Kusnir; Shahbaz Baig (Journal of University Medical & Dental College, 2024)
ABSTRACTThe present case report investigates the influence of SYNTHESIT dietary supplements on serum cholesterol levels in a 69-year-old male patient with dyslipidemia from Sevastopol, Russia. During the observation period, the patient’s cholesterol levels initially decreased after he began taking SYNTHESIT. However, this was followed by a slight increase in cholesterol levels as the supplement regimen continued. The results indicate that SYNTHESIT has an inconsistent effect on cholesterol; it lowers it at first and then causes a small increase over time. This case underlines the need for further studies to explore the long-term effects of SYNTHESIT on cholesterol management and its possible implications for dyslipidemia treatment strategies.